Stability Analysis for Assessment of Yield Performance and Adaptability of Selected Mango (Mangifera indica L.) Genotypes under Multi Location Trials in India - K, Sai Krishna; Chaudhary, Ram Kumar; Kumar, Mahesh (International Journal of Bio-resource and Stress Management, 2022)
A study was conducted in April 2020 based on the data collected from the All-India Coordinated Research Project on Sub-Tropical Fruits (AICRP-STF) and Central Institute for Subtropical Horticulture (CISH), Lucknow, India. The objective was to identify the high yielding and stable genotypes of mango using Additive main effects and multiplicative interaction (AMMI) and Genotype plus Genotype×Environment interaction (GGE) biplot analyses. Data on sixteen genotypes of mango tested across four locations, viz., Rewa, Sabour, Sangareddy, and Vengurla, over nine years was considered for the study. Combined analysis of variance showed highly significant differences (p<0.01) for genotype, environmental main effects and genotype×environment interaction (GEI) effects. The significant GEI contributes about 42.81% of the total sum of squares. AMMI analysis partitioned the GEI into fifteen interaction principal component axes and a residual term. The first two interaction principal component axes (IPCA1, IPCA2) collectively accounted for 40.80% of GEI sum of squares. AMMI analysis recommended Zardalu, Mankurad and GGE biplot analysis recommended Totapari, Mankurad as superior mango genotypes for cultivation in all the test locations. GGE biplot analysis classified the test locations into two mega environments. The first mega environment includes Rewa and Sangareddy with Neelum as the best suitable genotype; the second includes Vengurla and Sabour with Suvarnarekha as the best suitable genotype. The present study also concluded that GGE biplot analysis was the best analytical tool for identifying location-specific genotypes of mango, and AMMI analysis was the best for identifying superior genotypes having high yield with stability across all the test locations.